762 A combination of functional biomarkers improves identification of the tumor-specific reactive T cell repertoire. (10th December 2020) - Draghi, Arianna; Harbst, Katja; Svane, Inge; Donia, Marco
Abstract : Background: Detecting the entire repertoire of tumor-specific reactive T cells is essential for investigating the broad range of T cell functions in the tumor-microenvironment. At present, assays identifying tumor-specific functional activation measure either upregulation of specific surface molecules, de novo production of the most common antitumor cytokines or mobilization of cytotoxic granules. Methods: In this study, we combined transcriptomic analyses of tumor-specific reactive tumorinfiltrating lymphocytes (TILs), TIL-autologous tumor cell co-cultures and commonly used established detection protocols to develop an intracellular flow cytometry staining method encompassing simultaneous detection of intracellular CD137, de novo production of TNF and IFNy and extracellular mobilization of CD107a. Results: This approach enabled the identification of a larger fraction of tumor-specific reactive T cells in vitro compared to standard methods, revealing the existence of multiple distinct functional clusters of tumor-specific reactive TILs. Publicly available datasets of fresh tumor single-cell RNA-sequencing from four cancer types were investigated to confirm that these functional biomarkers identified distinct functional clusters forming the entire repertoire of tumor-specific reactive T cells in situ. Conclusions: In conclusion, we describe a simple method using a combination of functional biomarkers that improves identification of the tumor-specific reactive T cell repertoire in vitro and in situ.